Decreased attenuation difference between non-contrast and portal-venous phases of CT predicts the ultrasonography-unspecified adnexal torsion - Weili Xie; Zhongren Huang; Hongmei Kuang; Xiaoxing Li; Rixin Zhang; Wei Zeng; Cheng Jin; Junyuan Zhong; Jidong Peng; Weiling Cheng; Fuqing Zhou (Insights into Imaging)
Abstract Objectives To evaluate the value of contrast-enhanced CT in diagnosing ultrasonography-unspecified adnexal torsion (AT). Methods Surgically confirmed patients with painful pelvic masses (n = 165) were retrospectively collected from two institutes. Two senior radiologists independently reviewed the CT images and determined the Hounsfield unit difference between non-contrast vs portal venous phases (ΔHUPV-NC) in both derivation and validation samples. The cutoff value, sensitivity, specificity, predictivity, and reproducibility of the ΔHUPV-NC and other visually assessed CT signs were analyzed and compared using the receiver-operating characteristic curve, multivariable regression, and inter-rater agreement assays, respectively. Results Women with twisted (n = 73 [47 ± 19 years]) or untwisted (n = 92 [40 ± 15 years]) adnexal lesions were reviewed. The ΔHUPV-NC ≤ 17.5 HU (AUC: 0.91 [95% CI: 0.86, 0.96]; sensitivity: 95% [95% CI: 87, 98]; and specificity: 88% [95% CI: 80, 94]) was the independent predictor of AT (OR: 137 [95% CI: 39, 481], p < 0.001). After training in ΔHUPV-NC measurement, the agreement between two junior residents and the consensus increased from fair (resident-1: 0.29 [95% CI: 0.17, 0.41]; resident-2: 0.24 [95% CI: 0.1, 0.39]) to substantial (resident-1: 0.75 [95% CI: 0.65, 0.85]; resident-2: 0.72 [95% CI: 0.62, 0.83]). The post-training diagnostic accuracy (both residents: 81% [95% CI: 74, 87]) was higher than the pre-training accuracy (resident-1: 67% [95% CI: 59, 74], p = 0.007; resident-2: 66% [95% CI: 58, 73], p = 0.002). Conclusion The sign of ΔHUPV-NC ≤ 17.5 HU in contrast-enhanced CT can be used to predict the ultrasonography-unspecified AT. Critical relevance statement The decreased attenuation difference between non-contrast vs portal venous phases, a quantitative measurement-based CT sign, highlights the value of using contrast-enhanced CT as a second-line imaging approach after an equivocal ultrasonographic examination to diagnose AT in emergency settings. Key Points The value of contrast-enhanced CT in diagnosing ultrasonography-unspecified AT is underestimated. The ΔHUPV-NC ≤ 17.5 HU is the only predictor to diagnose the ultrasonography-unspecified AT. Contrast-enhanced CT can be used as a second-line imaging approach after an equivocal ultrasonographic examination. Graphical Abstract